Arabic-Only Language Time and Productive Skills in an Indonesian Pesantren - Baharun, Segaf; Mukhasibi, Abdullah; Rabbani, Syauqi (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2025)
ABSTRACT This study examines the effectiveness of Arabic-Only Language Time (AOLT) in enhancing the productive Arabic skills of students at Pesantren Darullughah Wadda’wah in East Java, Indonesia. The research aims to analyze how structured immersion practices influence students’ speaking fluency and writing accuracy within a pesantren sociocultural context. Using a qualitative case study design, data were collected through classroom observations, in-depth interviews, document analysis, and recordings of daily Arabic interactions. The findings indicate that AOLT significantly improves speaking fluency by increasing the frequency of spontaneous communication, fostering peer-driven correction, and reducing learners’ affective barriers. Writing proficiency also improves through greater lexical precision, syntactic accuracy, and enhanced coherence, largely supported by students’ expanded oral expression. The immersive setting of the pesantren characterized by communal discipline, hierarchical peer guidance, and consistent language enforcement plays a central role in amplifying learning outcomes. These results provide empirical evidence that immersive language environments rooted in cultural routines can produce robust linguistic gains. The study contributes to Arabic language pedagogy by highlighting immersion as a viable model for strengthening productive skills in Islamic educational institutions and recommends further research exploring quantitative measurements, digital immersion support, and comparative studies among various pesantren models. Keywords: language immersion; productive skills; Arabic language learning; pesantren environment.